AUTONOMOUS ENGLISH ACQUISITION IN BLENDED E-STUDIES FOR ADULTS FOR SUSTAINABLE DEVELOPMENT : ACTIVE RESEARCH - Bojāre, Ināra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Holistic approach is the main princip of sustainable development. Nevertheless investments of society in technological facilitation of learning mainly support developing of general skills. General and intellectual development of human’s personality follows from that. This research aims to evaluate methodological factors of English acquisition in classroom and virtual learning environment for facilitation of autonomous its acquisition in adults’ nonformal education. Hypothetically it is assumed that opportunities of learning environment of e-studies are insufficiently used for personal development in English acquisition programmes. The research presents an interpretation of learners’ and their facilitators evaluation of learning opportunities in classroom and virtual learning environment collected by SOT analysis. The study highlights vertical and horisontal transformation of values.